Educación ambiental: una alternativa para la conservación del manglar - Linares Mazariegos, Reyna Marisol; Tovilla Hernández, Cristian; De la Presa Pérez, Juan Carlos (Instituto de Ecología, A.C., 2016)
Mangroves constitutes an irreplaceable ecosystem, from which human communities extract diverse resources to survive. It is fundamental to inform the public about the importance of this ecosystem as a refuge of many species of the flora and fauna as well as its rational use. The environmental education is necessary to help in the awareness on the problematic that mangrove forests face at the present time. The activities of environmental education constitute part of the project Restauracion de areas de manglar impactadas por obras de dragado en el sistema lagunar de Chantuto initiated in April of 2003 by El Colegio de la Frontera Sur with funding from the Comision Nacional de Acuacultura y Pesca (CONAPESCA), at the Juan Escutia and Francisco Villa Elementary Schools in the Community of Santa Isabel, within the Reserva de la Biosfera La Encrucijada. The objective is that by using conferences, exhibition of videos, games and other activities, to create conscience in the children of elementary school level about the ecological and economic importance of the care and preservation of the resources of mangroves in benefit of the communities. The main subjects are: Mangrove and its resources, main impacts of the activities on the coastal zone, importance of the conservation, handling and restoration of the forests of mangrove, the coastal lagoons and estuaries, problematic of works of dredging on these systems, handling of the water, the soil, garbage and human well being, etc. Additionally by means of shops for the protection of mangrove it has been possible to involve senior citizens in this project, through activities that show the problematic and actions for a rational usage of mangrove and its resources.